PENGARUH RASIO TAPIOKA DENGAN RUMPUT LAUT Gracilaria sp. TERHADAP KARAKTERISTIK SOSIS IKAN LEMURU - Ilma Yaske E., Qurotul; Yusa, Ni Made; Ariyusasrini, Ni Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 6 No 1 (2017): Jurnal ITEPA, 2017)
This research was conducted to determine the effect ratio of tapioca and Gracilaria sp. to make the best characteristics of sardinella fish sausage. The research was using completely randomized design with ratio of tapioca and Gracilaria sp. as the treatment which consists of six levels, there were 100% : 0%, 80% : 20%, 60% : 40%, 40% : 60%, 80% : 20%, 0% : 100%. The observed parameters were water content, ash content, protein content, lipid content, carbohydrate content, crude fiber content, and sensory characteristics such as color, flavor, taste, texture, and overall acceptance. The results showed that the treatment characteristics of sardinella fish sausage, such as water content, ash content, lipid content, carbohydrate content, crude fiber content, and sensory characteristics such as color, taste, texture, and overall acceptance. The best ratio for producing the best characteristic of sardinella fish sausage was 80% tapioca : 20% Gracilaria sp. which had water content at 63.2%, ash content 2.29%, protein content 7.24%, lipid content 10.7%, carbohydrate content 16.59%, crude fiber content 6.1%, the color were slightly like, flavor were slightly like, taste were like, texture were like, and overall acceptance were like.
Keywords: sausage, sardinella, tapioca, Gracilaria sp.